The Effect of Nearpod Interactive Media on Learning Motivation of Law Department Students in the Indonesian Language Course - Risnawati; Maulidina, St. Nur; Fransisca, Rosalia (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study examines the effectiveness of utilizing Nearpod as an interactive learning media in increasing student learning motivation. The research method used is a quantitative method with a pre-experimental design approach. The population of the study were law students who took Indonesian language courses, with a sample of 36 first-semester law students selected using purposive sampling techniques. Data collection techniques include observation, questionnaires, and documentation to obtain relevant data. The results of the study indicate that the use of Nearpod as an interactive learning media significantly increases student learning motivation. This increase in motivation occurs through the use of interesting Nearpod features such as videos, slide shows, interactive games, and time-based activities such as